Post‐cataract surgery diplopia: aetiology, management and prevention. (September 2014) - Kalantzis, George; Papaconstantinou, Dimitris; Karagiannis, Dimitris; Koutsandrea, Chryssanthi; Stavropoulou, Dora; Georgalas, Ilias
<x xml:space="preserve">Abstract</x> Diplopia is an infrequent but distressing adverse outcome after uncomplicated cataract surgery. Many factors may contribute to the occurrence of this problem, including prolonged sensory deprivation resulting in disruption of sensory fusion, paresis of one or more extraocular muscles, myotoxic effects of local anaesthesia, optical aberrations (for example, aniseikonia) and pre‐existing disorders (for example, thyroid orbitopathy). The purpose of this review is to present the aetiology and clinical features of diplopia after cataract surgery and to discuss the possible modalities for the prevention and treatment of this frustrating complication.